2017
DOI: 10.1089/chi.2016.0334
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of a Multidisciplinary Weight Management Intervention for Youth with Disabilities

Abstract: Outcomes of the SNWMC revealed significant decreases in BMIz with <5 sessions on average over 12 months and indicated the increased efficacy of early intervention in youth with disabilities. Future research should continue to modify interventions for families with adolescent children with disabilities as well as investigate additional variables that may impact success in treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Because the primary TX‐CORD outcome study demonstrated minimal intervention effects within the 2 to 5 year‐old‐stratum compared with the older groups, the association of age with Latent Class 1 appears to be driven by weight status rather than intervention effect. Findings from other studies examining the relationship of age with intervention outcome are mixed, showing better effect with younger participants, older participants, or no relation with age . The studies varied in program structure, age range of participants, duration of program and follow‐up, the country where the study was done, and the developmental trajectory of the participants, hindering comparison.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the primary TX‐CORD outcome study demonstrated minimal intervention effects within the 2 to 5 year‐old‐stratum compared with the older groups, the association of age with Latent Class 1 appears to be driven by weight status rather than intervention effect. Findings from other studies examining the relationship of age with intervention outcome are mixed, showing better effect with younger participants, older participants, or no relation with age . The studies varied in program structure, age range of participants, duration of program and follow‐up, the country where the study was done, and the developmental trajectory of the participants, hindering comparison.…”
Section: Discussionmentioning
confidence: 99%
“…The studies varied in program structure, age range of participants, duration of program and follow‐up, the country where the study was done, and the developmental trajectory of the participants, hindering comparison. Of note, only a few studies of the association of age on intervention effect included children below age 5 years …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that an early intervention program to control weight would benefit these children. Pona et al [28] reported that after a program to control weight a significant interaction between child age and time of intervention revealed that younger children exhibited greater decreases in z-score body mass index over the treatment compared to older children.…”
Section: Resultsmentioning
confidence: 99%
“…This begins with counseling in the primary care setting for stage 1 and progresses to multidisciplinary services, medications, and bariatric surgery for those in stage 4 treatment 6 . Multidisciplinary weight management programs (MWMPs) have demonstrated success in weight reduction across a range of clinical settings and are frequently used to combat obesity at the patient level 7–9 . Assessment of readiness to change behaviors contributing to obesity is recommended at initiation of MWMP and is often informally performed as part of an overall motivational interviewing approach by the clinician during office visits 10 …”
mentioning
confidence: 99%